Nanolayered CoCrFeNi/Graphene Composites with High Strength and Crack Resistance - Xiaobin Feng; Ke Cao; Xiege Huang; Guodong Li; Yang Lu (Nanomaterials, 2022)
Emerging high-entropy alloy (HEA) films achieve high strength but generally show ineludible brittle fractures, strongly restricting their micro/nano-mechanical and functional applications. Nanolayered (NL) CoCrFeNi/graphene composites are elaborately fabricated via magnetron sputtering and the transfer process. It is uncovered that NL CoCrFeNi/graphene composite pillars exhibit a simultaneous ultra-high strength of 4.73 GPa and considerable compressive plasticity of over 20%. Detailed electron microscope observations and simulations reveal that the monolayer graphene interface can effectively block the crack propagation and stimulate dislocations to accommodate further deformation. Our findings open avenues for the fabrication of high-performance, HEA-based composites, thereby addressing the challenges and unmet needs in flexible electronics and mechanical metamaterials.